Impact of Oxygen on Pancreatic Islet Survival. Issue 5 (May 2018) - Komatsu, Hirotake; Kandeel, Fouad; Mullen, Yoko
Abstract : Abstract: Pancreatic islet transplantation is a promising treatment option for individuals with type 1 diabetes; however, maintaining islet function after transplantation remains a large challenge. Multiple factors, including hypoxia associated events, trigger pretransplant and posttransplant loss of islet function. In fact, islets are easily damaged in hypoxic conditions before transplantation including the preparation steps of pancreas procurement, islet isolation, and culture. Furthermore, after transplantation, islets are also exposed to the hypoxic environment of the transplant site until they are vascularized and engrafted. Because islets are exposed to such drastic environmental changes, protective measures are important to maintain islet viability and function. Many studies have demonstrated that the prevention of hypoxia contributes to maintaining islet quality. In this review, we summarize the latest oxygen-related islet physiology, including computational simulation. Furthermore, we review recent advances in oxygen-associated treatment options used as part of the transplant process, including up-to-date oxygen generating biomaterials as well as a classical oxygen inhalation therapy.